On Modeling Human Leukocyte Antigen–Identical Sibling Match Probability for Allogeneic Hematopoietic Cell Transplantation: Estimating the Need for an Unrelated Donor Source - Besse, Kelsey; Maiers, Martin; Confer, Dennis; Albrecht, Mark (Biology of blood and marrow transplantation, 2016)
Prior studies of allogeneic hematopoietic cell transplantation (HCT) therapy for the treatment of malignant or nonmalignant blood disorders assume a 30% likelihood that a patient will find a match among siblings and, therefore, a 70% likelihood of needing an unrelated donor source. This study utilizes birth data and statistical modeling to assess the adequacy of these estimates to describe the probability among US population cohorts segmented by race/ethnicity and age, including ages of greatest HCT utilization. Considerable variation in the likelihood of an HLA-identical sibling was found, ranging from 13% to 51%, depending upon patient age and race/ethnicity. Low sibling match probability, compounded with increased genetic diversity and lower availability among unrelated donors, put the youngest minority patients at the greatest risk for not finding a suitable related or unrelated HCT donor. Furthermore, the present 40-year decline in birth rates is expected to lead to 1.5-fold decrease in access to a matched sibling for today's young adults (18 to 44 years of age) when they reach peak HCT utilization years (near age 61 years) versus their contemporary adult counterparts (44 to 64 years). Understanding the sibling match probability by race/ethnicity and age cohort leads to forecasting the demand for unrelated HCT sources. •The average number of siblings for related hematopoietic cell transplantation donation differs by age and race.•The common sibling match estimate of 30% does not consider family size variations.•HLA-identical sibling match probabilities in the United States range from 13% to 51%.•Match likelihoods among adults ages 18 to 44 are 1.5 times lower than those ages 44 to 64.•Young minority patients are at greatest risk for not finding an HLA-matched donor.